Examining links from civic engagement to daily well-being from a self-determination theory perspective. Issue 2 (4th March 2019) - Wray-Lake, Laura; DeHaan, Cody R.; Shubert, Jennifer; Ryan, Richard M.
Abstract: Civic engagement may benefit individuals who engage in it, yet empirical evidence is lacking. We examined whether civic engagement was associated with well-being in a seven-day daily diary study of 276 college students. Based on self-determination theory, we hypothesized that satisfaction of basic psychological needs mediates the link between civic engagement and well-being. Four types of civic engagement – helping, pro-environmental behavior, volunteering, and charitable giving – were examined as separate predictors and as a composite predictor of daily well-being. The composite was associated with higher well-being across days, and basic needs satisfaction had a significant indirect effect on this association. Helping and pro-environmental behavior were linked to daily well-being directly and indirectly through basic needs satisfaction. No effects were evident for volunteering or charitable giving. Results suggest that civic engagement may enhance well-being, although some types of civic engagement may enhance well-being more than others.